Genetic characterization of a new candidate hemagglutinin subtype of influenza A viruses - Sasan Fereidouni; Elke Starick; Kobey Karamendin; Cecilia Di Genova; Simon D. Scott; Yelizaveta Khan; Timm Harder; Aidyn Kydyrmanov (Emerging Microbes and Infections, 2023)
Avian influenza viruses (AIV) have been classified on the basis of 16 subtypes of hemagglutinin (HA) and 9 subtypes of neuraminidase. Here we describe genomic evidence for a new candidate HA subtype, nominally H19, with a large genetic distance to all previously described AIV subtypes, derived from a cloacal swab sample of a Common Pochard (Aythya ferina) in Kazakhstan, in 2008. Avian influenza monitoring in wild birds especially in migratory hotspots such as central Asia is an important approach to gain information about the circulation of known and novel influenza viruses. Genetically, the novel HA coding sequence exhibits only 68.2% nucleotide and 68.5% amino acid identity with its nearest relation in the H9 (N2) subtype. The new HA sequence should be considered in current genomic diagnostic AI assays to facilitate its detection and eventual isolation enabling further study and antigenic classification.